2010
DOI: 10.1111/j.1365-277x.2010.01064.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in the effect of fish oil on appetite, inflammation and nutritional status in haemodialysis patients

Abstract: The results obtained demonstrate meaningful trends towards improvements in subjective appetite and certain inflammatory markers (although no change in dietary intake) and this effect was more pronounced in males. However, the levels of some inflammatory markers increased in females and this requires further study. The high level of adherence achieved indicates that an intervention requiring patients to consume four fish oil capsules per day is achievable. This was a short-term study and the effects need to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Although the FA compositions are typical and specific to each biological specimen, changes in FA profile in response to dietary manipulation have been demonstrated in intervention trials [ 10 ]. Studies in dialysis patients have shown that supplementation of marine n -3 PUFA resulted in incorporation of n -3 PUFA in total plasma [ 33 , 35 , 75 ], TAG [ 36 ], PL [ 66 , 74 ], and erythrocytes [ 32 , 75 ]. Apart from being a biomarker of dietary intake, circulating FAs also have major physiological roles.…”
Section: Discussionmentioning
confidence: 99%
“…Although the FA compositions are typical and specific to each biological specimen, changes in FA profile in response to dietary manipulation have been demonstrated in intervention trials [ 10 ]. Studies in dialysis patients have shown that supplementation of marine n -3 PUFA resulted in incorporation of n -3 PUFA in total plasma [ 33 , 35 , 75 ], TAG [ 36 ], PL [ 66 , 74 ], and erythrocytes [ 32 , 75 ]. Apart from being a biomarker of dietary intake, circulating FAs also have major physiological roles.…”
Section: Discussionmentioning
confidence: 99%
“…EPA and DHA have often been used to assess compliance to fish and fish oil intake in intervention studies [175179], and have been extensively associated with self-reported fish intake, measured either through 24-h dietary recalls or FFQs in a wide range of cohort and cross-sectional studies carried out in different populations [45, 180183]. Furthermore, EPA and DHA have been widely used to validate proposed FFQs for assessment of fish intake [83, 184187].…”
Section: Resultsmentioning
confidence: 99%
“…A quasi-experimental study 32 showed that the low dose omega-3 had no effect on CRP in the treatment group, but when patients were stratified for CRP levels and diabetes, the CRP levels decreased in elevated CRP and non-diabetes patients. An exploratory study 33 reported that fish oil affected inflammatory markers differently between men and women, with males maintaining or reducing CRP and IL-6 levels and females increasing levels of inflammatory markers. That may be associated with estrogen.…”
Section: Agreements and Disagreements With Other Studies Or Reviewsmentioning
confidence: 99%